2014
DOI: 10.5815/ijem.2014.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ni Doped ZnO Nanoparticles

Abstract: This paper discerns key ideas and themes of the possibility of growing Ni doped ZnO nanoparticles by electrochemical method. The purpose is to study the growth mechanism and to optimize the parameters of this method. Upon successful synthesizing the samples, they were characterized using various techniques. XRD, SEM, FTIR, photoluminescence spectroscopy together with the measured optical parameters obtained from UV-VIS absorption testing were analyzed. The X-ray diffraction (XRD) was measured by using a Bruker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…No signals of the metallic Zn are detected by XRD. However, there is no peak attributed to Ni, suggesting that the Ni +2 ion may be doped into ZnO 17 . It can be concluded from the results that incorporation of Co and Ni into ZnO lattice enhances crystalline quality.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…No signals of the metallic Zn are detected by XRD. However, there is no peak attributed to Ni, suggesting that the Ni +2 ion may be doped into ZnO 17 . It can be concluded from the results that incorporation of Co and Ni into ZnO lattice enhances crystalline quality.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…In the past few years, scientists have investigated the effect of ZnO nanoparticles doping with transition metals, such as Fe, Co, Ni and Mn [8][9][10][11][12][13][14][15][16][17][18][19][20]. Numerous theoretical explanations that have been proposed revealed that on doping ZnO nanoparticles with these transition elements results in dramatic changes in various luminescent and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction peak of each sample was strong, sharp and narrow that indicates the good crystalline nature of biosynthesised ZnO and Ni doped ZnO NPs [40]. The size of the particles (Table 4) was found to be in the range of the nanoparticle material size of 1 to 100 nm [32,41,42]. Lattice constants a, b, and c, inter planar angle and unit cell volumes were calculated by using Bragg's equation, λ = 2dsinθ and Lattice geometry equation [36].…”
Section: X-ray Diffraction Analysismentioning
confidence: 89%